Residue determination of plant activator benzo‐1, 2, 3‐thiadiazole‐7‐ carboxylic acid 2‐benzoyloxyethyl ester in water, soil, and vegetable by gas chromatography with tandem mass spectrometry. Issue 11 (27th April 2015) - Shuying, Li; Yihu, Wang; Qianqian, Sun; Wenjun, Gui; Guonian, Zhu
<x xml:space="preserve">Abstract</x> This study aimed to develop a rapid, specific and sensitive method for the residue determination of benzo‐1, 2, 3‐thiadiazole‐7‐carboxylic acid 2‐benzoyloxyethyl ester in soil, vegetable, and water by using gas chromatography with tandem mass spectrometry. During the extraction procedure, modified quick, easy, cheap, effective, rugged, and safe method using acetonitrile was compared with classical oscillating extraction using ethyl acetate and acetone, respectively. Before injection, a solid‐phase extraction cartridge of Bond Elut Florisil was used for sample clean‐up. The method was fully validated and showed satisfactory linearity (r2 > 0.99) over the range to be assayed (10–1000 ng/mL), with the limits of detection ranging from 0.092–0.229 ng/mL and the limits of quantification ranging from 0.307–0.763 ng/mL. Recovery values at the spiked concentrations of 10, 100 and 1000 ng/g varied from 85.9–109.3%, 81.0–108.2%, 74.2–113.4% for water, soil and vegetable, respectively, with the maximum relative standard deviations of 12.2%. Results indicated that the established modified quick, easy, cheap, effective, rugged, and safe method coupled to gas chromatography with tandem mass spectrometry was promising for the residue monitoring of benzo‐1, 2, 3‐thiadiazole‐7‐carboxylic acid 2‐benzoyloxyethyl ester in the environment and vegetable products.